Benthic dinoflagellate diversity and mixotrophy: Prorocentrum - Mohammad Noor, Normawaty; Moestrup, Ojvind (2011)
Marine benthic dinoflagellates can be found in many different habitats including seaweeds, dead coral and sediments. New species are continuously being described based on morphology and molecular approaches, this is obviously a type of organisms which has been overlooked in many parts of the world. However, subsequent identifications by other researchers are sometimes vague, probably because the original species descriptions are incomplete and lack sufficient detail. An example is the genus Prorocentrum. The genus was established in 1834 by Ehrenberg with Prorocentrum micans as type species. During the subsequent 175 years more than 20 species have been described. There is, however, some overlap in some species descriptions, an example being P. concavum and P. arabianum. In this paper, problems encountered in identification of Prorocentrum species will be discussed. The phylogenetic relationship between Prorocentrum and other dinoflagellates has not been resolved, even using molecular methods, and the Prorocentrum group presently occupies an isolated position within the dinoflagellates. Besides, the potential of dinoflagellates, in general as mixotrophy will be discussed